Investigating grade 10 geography teachers' implementation of a learner-centred approach in selected Namibian schools - Angula, Adelheid (Rhodes University, Faculty of Education, Department of Education, 2007)
Geography, more than other subjects in the curriculum, plays a central role in general education in equipping learners with skills and competencies needed for modern living and global citizenship. A learner-centred education in Namibia was adopted to provide more opportunities for learners to develop the required skills and competencies irrespective of their different cultural background. This small-scale case study investigated three Grade 10 geography teachers' understanding and implementation ofa learner-centred approach to gain insights into how leamer-centred education is being implemented in the context of Geography. The research design adopted a qualitative approach within an interpretative orientation. Data were collected through interviews, classroom observations and documentary analysis. The research was conducted at three selected schools in Oshikoto Region with three Grade 10 geography teachers The findings revealed, firstly, that teachers have a limited understanding of the key ideas ofLCE, such as, prior knowledge, role of questioning, and social interaction in learning; use of resources and the types of assessment activities which comply with the aims of LCE. Seconclly, the findings revealed that the policy documents, such as syllabuses, that are being used by the participants are not in line with the tenets ofLCE. Thirdly, teachers appeared to have limited subject knowledge, as revealed by their lack of understanding of how to translate the aims and assessment objectives into their daily lessons. The study therefore raises some possibilities for improving the implementation of LCE in the selected schools if the gaps as identified by this study are reduced.
Keywords: Geography -- Study and teaching (Secondary) -- Namibia; Student-centered learning -- Namibia